Spatiotemporal single-cell RNA sequencing of developing chicken hearts identifies interplay between cellular differentiation and morphogenesis - Madhav Mantri (Nature Portfolio, 2021)
Using single-cell and spatial transcriptomics in chicken hearts, here, the authors generate a census of cellular interactions from early to late four-chambered heart stage, identifying a distinct epicardial-mesenchymal cell population with a migratory phenotype.